Perspectives of Bamboo Blight in Bangladesh - Rahman, M. A. (Indian Forester, 1988)
A review of major finding of various authors on bamboo blight is presented. Bamboo blight is a major disease in village groves. It only occurs in Bangladesh. Blight attacks young bamboos during or soon after the elongation growth. Symptoms have been described. A fungus, Saroclodium oryzae is associated with early blight symptoms. Secondary insect infestation aggravates the damage. Disease losses are highest in Bombusa vulgaris followed by B. balcooa and Jawa/Kata Jail variety of B. tulda. These are most Common bamboos in the village groves. Blight can kill clumps of B. vulgaris in 3-4 years. Height of healthy portion of larger percentage of blighted B. vulgaris is very short compared to the healthy ones. Improved cultural measures and drenching of soil of the affected clumps with a fungicide, Dithane M 45, before monsoon improve survival of new culms. Lines for further research on bamboo blight are suggested.